2021
DOI: 10.1101/2021.07.15.452518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping inter-individual functional connectivity variability in TMS targets for major depressive disorder

Abstract: Transcranial magnetic stimulation (TMS) is an emerging alternative to existing treatments for major depressive disorder (MDD). The effects of TMS on both brain physiology and therapeutic outcomes are known to be highly variable from subject to subject, however. Proposed reasons for this variability include individual differences in neurophysiology, in cortical geometry, and in brain connectivity. Standard approaches to TMS target site definition tend to focus on coordinates or landmarks within the individual b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In this work, we showed that given a target of interest, computational optimization can be used maximize the E-field delivery to the target. More sophisticated algorithms have been proposed to combine individual functional connectivity patterns, and E-field optimization, to determine coil placements that would not only maximize local stimulation, but also account for downstream effects of TMS, i.e., to maximize brain network engagement [58,59,60,61]. Systematic clinical trials are needed to prospectively compare the antidepressant efficacy of these strategies in adults and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we showed that given a target of interest, computational optimization can be used maximize the E-field delivery to the target. More sophisticated algorithms have been proposed to combine individual functional connectivity patterns, and E-field optimization, to determine coil placements that would not only maximize local stimulation, but also account for downstream effects of TMS, i.e., to maximize brain network engagement [58,59,60,61]. Systematic clinical trials are needed to prospectively compare the antidepressant efficacy of these strategies in adults and adolescents.…”
Section: Discussionmentioning
confidence: 99%